Introduction - Birkemeyer, Karen; Carr, Mike; Manley, Paul; Meisner, Mark; Naherniak, Craig; Pearee, Jacqueline; Sahanatien, Vicki; Struthers, Rolf; Weegar, Tom (UnderCurrents: Journal of Critical Environmental Studies, 1989)
Welcome to the first issue of Undercurrents. This journal is the initiative of a group of graduate students at the Faculty of Environmental Studies at York University. Our motivation to publish a journal comes from a realization of the need for a forum to present critical and innovative graduate student work in the area of environmental studies. This, however, is an area of great diversity and a glance at the table of contents may leave some readers re-examining their assumptions about their notion of "environment." Indeed, it is the philosophy of Undercurrents to pursue the widest possible understanding of environment.